High-Intensity Interval Training Improves Cardiac Function by miR-206 Dependent HSP60 Induction in Diabetic Rats - Delfan, Maryam; Amadeh Juybari, Raheleh; Gorgani-Firuzjaee, Sattar; Høiriis Nielsen, Jens; Delfan, Neda; Laher, Ismail; Saeidi, Ayoub; Granacher, Urs; Zouhal, Hassane (Frontiers in Cardiovascular Medicine, 2022)
Objective: A role for microRNAs is implicated in several biological and pathological processes. We investigated the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on molecular markers of diabetic cardiomyopathy in rats. Methods: Eighteen male Wistar rats (260±10 g; aged eight weeks) with streptozotocin (STZ)-induced type 1 diabetes mellitus (55 mg/kg, IP) were randomly allocated to three groups: control, MICT, and HIIT. The two different training protocols were performed five days each week for five weeks. Cardiac performance (end-systolic and end-diastolic dimensions, ejection fraction), the expression of miR-206, HSP60, and markers of apoptosis (cleaved PARP and cytochrome C) were determined at the end of the exercise interventions. Results: Both exercise interventions (HIIT and MICT) decreased blood glucose levels and improved cardiac performance, with greater changes in the HIIT group (p<0.001, 2: 0.909). While the expressions of miR-206 and apoptotic markers decreased in both training protocols (p<0.001, 2: 0.967), HIIT caused greater reductions in apoptotic markers and produced a 20% greater reduction in miR-206 compared with the MICT protocol (p<0.001). Furthermore, both training protocols enhanced the expression of HSP60 (p<0.001, 2: 0.976), with a nearly 50% greater increase in the HIIT group compared with MICT. Conclusions: Our results indicate that both exercise protocols, HIIT and MICT, have the potential to reduce diabetic cardiomyopathy by modifying the expression of miR-206 and its downstream targets of apoptosis. It seems however that HIIT is even more effective than MICT to modulate these molecular markers.